THE INFLUENCE OF INCOME AND FINANCIAL LITERACY ON INVESTMENT DECISION THROUGH FINANCIAL BEHAVIOR AS A MODERATING VARIABLE - Yeni, Fitri; Sarah, Siti; Ramadhan, Muhammad Fikri; Sari, Putri Intan Permata (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study aims to discover the influence of income and financial literacy on investment decisions through financial behavior as a moderating variable for Bank Nagari Muara Labuh Branch customers. The sample in this study were customers of Bank Nagari with a total of 100 samples. The data analysis method uses moderated regression analysis The results are based on the research and hypothesis testing that has been done, the results of the study can obtain that income has a positive and significant effect on Investment Decisions at Bank Nagari Muara Labuh Branch. Financial Literacy positively and significantly affects Investment Decisions at Bank Nagari Muara Labuh Branch. Income positively and significantly affects Investment Decisions through Financial Behavior at Bank Nagari Muara Labuh Branch. Financial Literacy positively and significantly affects Financial Behavior Decisions at Bank Nagari Muara Labuh Branch. This research contributes to financial institutions to create policies to improve customer investment decisions. For the government, this research contributes to making policies in setting regional minimum wages Keywords: Income, Financial Literacy, Investment Decisions, Financial Behavior